Shape and Site Dependent in Vivo Degradation of Mg-Zn Pins in Rabbit Femoral Condyle - Han, Pei (Molecular Diversity Preservation International (MDPI), 2014)
A type of specially designed pin model of Mg-Zn alloy was implanted into the full thickness of lesions of New Zealand rabbits’ femoral condyles. The recovery progress, outer surface healing and in vivo degradation were characterized by various methods including radiographs, Micro-CT scan with surface rendering, SEM (scanning electron microscope) with EDX (Energy Dispersive X-ray analysis) and so on. The in vivo results suggested that a few but not sufficient bridges for holding force were formed between the bone and the implant if there was a preexisting gap between them. The rapid degradation of the implantation in the condyle would result in the appearance of cavities. Morphological evaluation of the specially designed pins indicated that the cusp was the most vulnerable part during degradation. Furthermore, different implantation sites with distinct components and biological functions can lead to different degradation rates of Mg-Zn alloy. The rate of Mg-Zn alloy decreases in the following order: implantation into soft tissue, less trabecular bone, more trabecular bone, and cortical bone. Because of the complexities of in vivo degradation, it is necessary for the design of biomedical Mg-Zn devices to take into consideration the implantation sites used in clinics.